2002
DOI: 10.1074/mcp.m200043-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics of Synechocystis sp. Strain PCC 6803

Abstract: Cyanobacteria are unique prokaryotes since they in addition to outer and plasma membranes contain the photosynthetic membranes (thylakoids). The plasma membranes of Synechocystis 6803, which can be completely purified by density centrifugation and polymer two-phase partitioning, have been found to be more complex than previously anticipated, i.e. they appear to be essential for assembly of the two photosystems. A proteomic approach for the characterization of cyanobacterial plasma membranes using two-dimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(85 citation statements)
references
References 75 publications
(77 reference statements)
5
79
1
Order By: Relevance
“…For example, in this organism ZnuA has a transmembrane ␣-helix, whereas MntC is tethered via a lipid anchor (5,6). FutA1 is a predicted lipoprotein (41,42), although there has been some debate about its association with thylakoid versus plasma membranes (43,44). Crucially, FutA1 has never been observed in soluble periplasmic extracts (40,43).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in this organism ZnuA has a transmembrane ␣-helix, whereas MntC is tethered via a lipid anchor (5,6). FutA1 is a predicted lipoprotein (41,42), although there has been some debate about its association with thylakoid versus plasma membranes (43,44). Crucially, FutA1 has never been observed in soluble periplasmic extracts (40,43).…”
Section: Discussionmentioning
confidence: 99%
“…PCC6803 as a start point, but expressing this as a membrane protein in E. coli for which there were no identified orthologues. The protein has an undetermined function but has been identified in the plasma membrane of Synechocystis [43], with the predicted gene product consisting of 673 amino acids with a single predicted transmembrane alphahelix close to the N-terminus. A portion of the sll1021 sequence coding for 38 amino acids including the predicted transmembrane alpha-helix was fused in-frame to the gene coding for GFPmut3* [44] with a linker of five asparagine residues.…”
Section: Materials and Methods (A) Bacterial Cell Strain And Preparationmentioning
confidence: 99%
“…Mackey et al (2013) and Pittera et al (2014) have shown a similar decrease in D1 protein expression in tropical isolates at low temperatures correlating with lower growth rate. D1 is sensitive to environmental stress and susceptible to photo-oxidative damage and requires replacement through a continuous repair cycle for the maintenance of photosynthesis (Huang et al, 2002). In freshwater cyanobacteria, to overcome low temperature-induced inhibition of the repair cycle, increased membrane fluidity and de novo protein synthesis are required (Kanervo et al, 1997;Suzuki et al, 2001;Murata et al, 2007;Tyystjärvi et al, 2001).…”
Section: Molecular-level Adaptations To Growth Temperaturementioning
confidence: 99%